Civil Technology Teacher’s Environmental Knowledge in Promoting Active Learning During Practical Lessons: A South African perspective - Isaac , Mtshali Thokozani; Manto , Ramaligela Sylvia (Online Journal for TVET Practitioners, 2019)
Environmental knowledge refers to a well-managed, safe, learner-centred, practical learning environment that is conducive to hands-on skills learning. For this knowledge to be effective, teachers need to demonstrate competency in practical tasks such that learners are ready for trade industries upon their schooling completion. The purpose of this study was to investigate Civil Technology teacher’s environmental knowledge in promoting active learning during practical lessons. Purposive sampling was used to select a total of 63 learners and 5 teachers to participate in this study. Observation and interview instruments were used as data-collection methods. This study employed Stronge qualities of effective teachers as a conceptual framework. The study found that Civil Technology teachers have several challenges in their environmental knowledge that hinders the promotion of active learning. All teachers indicated that they do not do lesson planning and they rarely check on the ones done by DBE. This practice hampers the promotion of active learning in a sense that teachers do not know the extent to which they could engage their learners in practical tasks without wasting time and consumables. All this challenges contribute to the ongoing challenge of producing learners without practical skills necessary for the workplace. This study calls for engineering sectors, higher education institutions, department of basic education as well teachers and subject advisors to continually review teachers pedagogical knowledge and find better ways of improving in-service teachers teaching strategies.